Influence of different processing parameters in physical and sensorial properties of Serra da Estrela cheese - Correia, Paula (2014)
Introduction: Cheese is a classical dairy product, which is strongly judged by its appearance, flavour and texture. Processing parameters that could affect cheese structure play a dominant role upon the features exhibited by the final product. Serra da Estrela cheese is a DOP cheese manufactured from raw ewes’ milk and curdled with thistle flowers aqueous extract. The aim of this study was the evaluation of physical and sensorial properties of cheeses, produced with thistle flowers from different ecotypes and added in different quantities to milk from sheep breed. Other variable factors were salt quantity and ripening moisture. Materials and methods: Two dairies were involved in this study: ANCOSE and Quinta das Lameiras. The chemical composition of sheep milk was determined for all cheese batches. The clotting time, the evolution of weight and colour, the texture and sensorial characteristics of cheeses were evaluated. Results: Both dairies presented similar chemical sheep milk composition. The clotting time is independent of the quanties of thistle aquous extracts added to the milk, and it is similar for both dairies, varaing from 36-47 minutes. The loss of weight showed a similar decreasing tendency but with quite different values. Generally, the thistle flower ecotype didn’t influence the L and b*colour parameters during the ripening process and in the final product, but there was a significant influence on a* parameter. The textural analysis results reveal significant differences between the two dairies for the same thistle flower ecotype, considering the crust and inner firmness, stickiness and adhesiveness. Cheeses presented different sensorial properties, considering the different processing parameters studied. Conclusions: Serra da Estrela cheese produced in both dairies presented different physical and sensorial properties, meaning that with a strong knowledge of the properties assigned by these different flower extracts and with the control of some processing parameters it is possible to produce a specific cheese attending to different consumer targets.